Argentobaumhauerite: name, chemistry, crystal structure, comparison with baumhauerite, and position in the Lengenbach mineralization sequence. (2nd January 2018) - Topa, Dan; Makovicky, Emil
Abstract: The crystal structure of argentobaumhauerite is reported for the first time from a sulfosalt aggregate from Lengenbach deposit, Binntal, Switzerland. The chemical formula of argentobaumhauerite, calculated in agreement with the results of structure determination is Cu0.06 Ag1.20 Tl0.18 Pb21.46 Sb0.56 As32.28 S72.26 . The difference from the idealized baumahuerite formula, Pb12 As16 S36, and from the formula of Ag –, Tl- and Sb-free baumhauerite from Moosegg, Austria, Pb11.80 As16.28 S35.92, expresses the Ag + As and Tl + As substitution for 2Pb. Argentobaumhauerite is triclinic, a = 7.9053(10), b = 8.4680(10), c = 44.4102(53) Å, α = 84.614(2), β = 86.469(2), γ = 89.810(2)°. V (cell) = 2954.16 Å3, space group P1. Baumhauerite Pb11.80 As16.28 S35.92 from Moosegg is triclinic, a = 7.884(4), b = 8.345(4), c = 22.811(11) Å, α = 90.069(8), β = 97.255(8), γ = 90.082(8)°, V (cell) = 1488.8(13) Å 3, space group P1. Both minerals represent the N 1, 2 = 3;4 = 3.5 member of the sartorite homologous series, with As-rich slabs separated by zigzag layers of trigonal coordination prisms of lead. In argentobaumhauerite the sequence of alternating N = 3 and N = 4 slabs of baumhauerite is further modified by alternation of two distinct types of N = 4 slabs, those with Pb present in the slab interior and those with the interior Pb substituted by Ag + As. The length and arrangement of crankshaft chains of short As–S bonds differs between different slabs, and especially between the N = 4 slabs of baumhauerite and argentobaumhauerite. The name 'argentobaumhauerite' replaces the preliminary name 'baumhauerite-2 a ' (IMA-CNMNC; accepted proposal 15-F).